Analisis Tata Kelola Pemerintahan Desa dalam Upaya UMKM di Desa Sajen, Kecamatan Pacet Kabupaten Mojokerto: Analysis of Village Governance in Efforts to Empower MSMEs in Sajen Village, Pacet District Mojokerto Regency - Hikmah Muhaimin; Revi Firmala; Elsa Nur Aini; Khisamuddin Khisamuddin; Faisal Mubarok; Nugroho Rendi (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2023)
Sajen Village. Pacet Sub-District and Mojokerto Regency were the target research locations. This research is to find out how the management of human resources in government affects UMKM growth in Sajen Village, Pacet District, and Mojokerto Regency. This study used a qualitative methodology, and the informants were approached directly. Data collection techniques include observation and interviews; descriptive research is the methodology employed. The findings of this study indicate that the village government program in Sajen Village to develop UMKM has actually helped the surrounding community in developing their businesses. Not only the community, but the Sajen Village Government has also received attention from other villages. The Mojokerto Regency Government is no exception and pays attention to and appreciates the management of human resources in the Sajen Village Government because it has developed its UMKM program with village communities, which in the end can be implemented and the community can also improve its economy. The Sajen Village Government also experienced problems or obstacles in carrying out this program due to a lack of community initiative to participate in activity events held by the village government